The attitude of Polish consumers toward food irradiation as one of the methods of food preservation - Buczkowska, Marta; Dudczak, Anna; Szajnoga, Dominika; Górski, Michał; Malinowska-Borowska, Jolanta; Kulik, Aleksandra; Szczyrba, Anna (Frontiers in Public Health, 2023)
Background Food irradiation is one of the methods of food preservation. Unfortunately, despite many opinions from national and international organizations that confirm the safety of the irradiation technique, the irradiated food market is slowly developing, which is particularly noticeable in European countries, including Poland. Objectives The main objective of this study was to determine the attitude of Polish consumers toward irradiated food and to find out whether familiarizing the respondents with educational materials on the irradiation technique would change their attitudes. Material and methods In response to the objective of the study, an online survey (with the presentation of educational materials) was conducted with 609 respondents living in the Silesian Voivodeship, Poland. A specially prepared author's questionnaire was used, containing questions relating to: sociodemographic data, food preservation, food irradiation. An integral part of the survey was a multimedia presentation containing information about the food irradiation process. Results A low level of knowledge about food irradiation was found-−90.31% (n = 550) of the respondents had never heard of this method of preservation before. The percentage of respondents with a positive attitude toward radiation-preserved products increased significantly after providing informative material, from 6.20 (n = 38) to 67.16% (n = 409). The final attitude of the respondents toward irradiated food varied and depended on age, education and place of residence—positive attitudes toward irradiation predominated among those who were young (<30 years old), had a higher education and lived in cities >100,000 inhabitants. Educational materials also had a significant impact on consumers' interest in purchasing irradiated food—the percentage of people declaring a willingness to purchase this type of product increased from 19.20 (n = 117) to 59.30% (n = 361). Almost 60% of the respondents were willing to purchase irradiated foods. Women, on average, were more likely to be interested in purchasing irradiated food compared to men. Conclusions The survey indicates that irradiated food could be commercially introduced in Poland, but on the condition that an effective educational program is planned.